Analysis of the current status of rehabilitation motivation and its influencing factors in older adults with stroke: a cross-sectional study - Tan, Mingyang; Li, Hongyu; Wang, Xiuli (Frontiers in Aging Neuroscience, 2023)
Objective: Among stroke patients, exercise adherence is an important factor in reducing the rate of physical disability and mortality. Rehabilitation exercise after stroke is a safe and effective measure to restore normal body functions, but the analysis of factors influencing patients' motivation for rehabilitation is not well established. Therefore, this study will explore the influencing factors of rehabilitation motivation in older adults with stroke so as to reduce the disability rate of stroke. Method: A convenience sampling method was used to study 350 patients in a stroke ward of a tertiary care hospital in Jinzhou, Liaoning Province. Patients' general demographic data, Multidimensional Scale of Perceived Social Support (PSSS), Questionnaire of Exercise Adherence (EAQ), Tampa scale of kinesiophobia (TSK-11), and Motivation in stroke patients for rehabilitation scale (MORE) were assessed. ANOVA or t-test analysis, correlation analysis, and linear regression analysis were used to explore the factors influencing the motivation for rehabilitation in older adults with stroke. Results: The results showed that stroke patients' motivation for rehabilitation was at a moderate level. Perceived social support, exercise adherence, and stroke motivation was positively correlated (r=0.619, P<0.01; r=0.569, P<0.01), and kinesiophobia was negatively correlated with stroke motivation (r=-0.677, P<0.01). Time of stroke, location of the lesion, perceived social support, exercise adherence, and kinesiophobia are influential factors affecting patients' motivation to recover. Conclusions: In the rehabilitation program for older adult patients with stroke, healthcare providers should specify targeted rehabilitation measures according to the different degrees of the patient's condition, so as to improve the effectiveness of rehabilitation medical implementation.